2002
DOI: 10.1006/dbio.2001.0525
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Regulation of pEg3, a New Xenopus Protein Kinase of the KIN1/PAR-1/MARK Family

Abstract: We report the characterization of pEg3, a Xenopus protein kinase related to members of the KIN1/PAR-1/MARK family. The founding members of this newly emerging kinase family were shown to be involved in the establishment of cell polarity and both microtubule dynamic and cytoskeleton organization. Sequence analyses suggest that pEg3 and related protein kinases in human, mouse, and Caenorhabditis elegans might constitute a distinct group in this family. pEg3 is encoded by a maternal mRNA, polyadenylated in unfert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 38 publications
6
95
0
Order By: Relevance
“…This residue was chosen after alignment with the Xenopus MELK protein kinase for which the corresponding K42R mutation led to a kinase dead enzyme. 44 The mutagenized Kin1-K154R Open Reading Frame was inserted into pREP41GFP in NdeI cloning sites and sequenced. Kin1Δ cells transformed with pREP41GFP-Kin1-K154R were not rescued (data not shown), indicating that the kinase activity of Kin1 is required to fulfil its cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…This residue was chosen after alignment with the Xenopus MELK protein kinase for which the corresponding K42R mutation led to a kinase dead enzyme. 44 The mutagenized Kin1-K154R Open Reading Frame was inserted into pREP41GFP in NdeI cloning sites and sequenced. Kin1Δ cells transformed with pREP41GFP-Kin1-K154R were not rescued (data not shown), indicating that the kinase activity of Kin1 is required to fulfil its cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction mixtures (20 µl) containing 600 ng CDC25B3 were incubated for 1 h at 30˚C with or without wild type or kinase-dead purified recombinant Eg3, 20 together with 50 µM ATP in kinase buffer except that the pH was raised to 8.2 to stabilize CDC25B. 29 A 10 µl aliquot of each reaction was then loaded onto a 10:0.13% acrylamide:bis-acrylamide gel for electrophoresis, and the remainder of each reaction was used to measure CDC25B phosphatase activity using FDP as the substrate.…”
Section: Antibodiesmentioning
confidence: 99%
“…17,18 We recently reported that CDC25B is phosphorylated on serine 323 by pEg3, a cell cycle-regulated protein kinase of the KIN1/PAR-1/MARK family. 19,20 This residue is equivalent to serine 216 of CDC25C, whose phosphorylation creates a 14.3.3 binding site that plays a critical role in the inactivation of CDC25C that occurs upon checkpoint activation after DNA damage. 21 We demonstrated that pEg3 is able to specifically associate with CDC25B in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The KIN1/PAR-1/MARK protein family is composed of eukaryotic serine/threonine protein kinases that are predominantly conserved from yeasts to human in their N-terminal kinase catalytic domain and in the 40 C-terminal amino acids (Blot et al, 2002;Böhm et al, 1997;Drewes et al, 1998). In Caenorhabditis elegans, the par-1 gene was isolated in a genetic screen for par ("partitioning defective") mutations that led to the inability of one-cell stage embryo to partition asymmetrically cell fate determinants.…”
Section: Introductionmentioning
confidence: 99%